Advance Treatment of Leachate Generated From Solid Waste - Rahul Gupta; Farhin Khan; Sarita Sharma (AG Volumes, 2021)
As we all know that several of tons municipal solid waste (MSW) is generated in India per year which is very difficult to handle and treat. Organic and inorganic waste, e-waste, used papers, wood, plastic glass, leather, rubber etc. comes under the municipal solid waste (MSW). For the treatment of the MSW we use landfill method which causes threat to the water bodies, eventually harming the environment, ecosystem as well as living beings. The   most common and most focused studies observed in many technical papers related to this problem mostly deals with the management and treatment efficiency of solid waste leachate. This review paper aims to put forward an overview of solid waste leachate, it's characteristics, composition, contaminants to the ground water, effects on mankind and environment, current scenario of landfill technology in India, various treatment methods.